PERAN PENDIDIKAN DALAM PROSES PERUBAHAN SOSIAL DI DESA TUMALUNTUNG KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Indy, Ryan; Waani, Fonny J.; Kandowangko, N. (HOLISTIK, Journal Of Social and Culture, 2019)
Education provides the advancement of human thought, so that their level of life increases. Nowadays the development of the era has brought the impact of change in various aspects. The impact of changes that occur so quickly and easily observed is the social aspect. The social change is not just heading towards progress, but it can also lead to setbacks. It has been happening since ancient times. There are times when the changes occurred so rapidly, that it confuses the human being to deal with it. Any change occurring in the community always raises the risk of social life or social uncertainty.The function of education in social change in order to improve the ability of learners that critical analysis plays a role to instill new beliefs and values on the way people think. Education in the modern century has succeeded in creating a new generation with the power of creativity and the ability of critical thinking, attitudes are not easy to give in to the situation and replaced with attitudes that are willing to change. These ways of thinking and attitudes will escape dependence on the help of others. Thus learners besides as understanding the changes in social life can also as agents change themselves. In fact, the community of educated Tumaluntung village is still less involved in government and family drive.Keywords: education, change, social